2013
DOI: 10.1016/j.joca.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Spinal nociceptive reflexes are sensitized in the monosodium iodoacetate model of osteoarthritis pain in the rat

Abstract: We demonstrate that spinal nociceptive reflex pathways are sensitized following the development of OA, suggesting the presence of central sensitization. Further, our data reflect OA-induced alterations in the descending control of reflex responses. Our findings contribute to a mechanism-based understanding of OA pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 41 publications
3
33
0
Order By: Relevance
“…Recent studies have advanced understanding of the spinal mechanisms contributing to OA pain behaviour, demonstrating important contributions of dorsal horn neuronal excitability (Sagar et al, ; Kelly et al, ) and activation of spinal glia cells (Lee et al, ; Sagar et al, ; Ogbonna et al, ; Yu et al, ) (see references in Rani Sagar et al, ). In the present study, repeated MJN110 treatment did not significantly inhibit MIA‐induced increases in GFAP mRNA in the dorsal horn of the spinal cord, which contrasts with the reported effects of an exogenous cannabinoid ligand selective for the CB 2 receptor (Burston et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have advanced understanding of the spinal mechanisms contributing to OA pain behaviour, demonstrating important contributions of dorsal horn neuronal excitability (Sagar et al, ; Kelly et al, ) and activation of spinal glia cells (Lee et al, ; Sagar et al, ; Ogbonna et al, ; Yu et al, ) (see references in Rani Sagar et al, ). In the present study, repeated MJN110 treatment did not significantly inhibit MIA‐induced increases in GFAP mRNA in the dorsal horn of the spinal cord, which contrasts with the reported effects of an exogenous cannabinoid ligand selective for the CB 2 receptor (Burston et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These are accompanied by changes in the expression of pain-mediating cytokines in the DRG and spinal cord which correlate with the development of hyperalgesia and allodynia (Im et al, 2010). The same model causes reduced nociceptive thresholds in the biceps femoris which neurophysiologically represents a spinal mechanism (Kelly et al, 2013). The monoiodoacetate (MIA) model also seems capable of activating spinal glial cells which may contribute to the development and maintenance of CS (Sagar et al, 2011).…”
Section: Osteoarthritis (Oa) Painmentioning
confidence: 99%
“…CZ extract increased the induction of HO-1 and inhibited IL-1β, IL-6, and cyclooxygenase-2 mRNA levels in LPS-stimulated RAW264.7 cells. 12,25) Recently, Kim et al reported that extract from CZ ameliorated arthritis symptoms and bone erosion in collageninduced rheumatoid arthritis. 17) Here, we demonstrated the protective effect of BST106 against OA-related cartilage damage.…”
Section: Discussionmentioning
confidence: 99%